2017
DOI: 10.1177/0333102417732504
|View full text |Cite
|
Sign up to set email alerts
|

Late-Breaking Abstracts of the 2017 International Headache Congress

Abstract: Objectives: Pain experienced in migraine involves the sensitization of trigeminal afferent neurons, but the extraordinary cellular diversity within trigeminal ganglia has limited our understanding of the molecular substrates through which this process occurs. Recent advances in single-cell RNA sequencing technology have enabled the massively parallel identification and molecular profiling of nearly all cells within heterogeneous tissues. We are using this powerful tool to identify unique gene expression patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…23 Efficacy results from this study confirmed those reported in phase 2 studies, 17,18 and the treatment duration was twice as long in this study (6 months vs 3 months). These results were replicated in a similarly designed study (EVOLVE-2) 29 in which 915 patients were randomized and received at least 1 dose of IP.…”
Section: Discussionmentioning
confidence: 76%
“…23 Efficacy results from this study confirmed those reported in phase 2 studies, 17,18 and the treatment duration was twice as long in this study (6 months vs 3 months). These results were replicated in a similarly designed study (EVOLVE-2) 29 in which 915 patients were randomized and received at least 1 dose of IP.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the placebo response rate for 2‐hour MBS freedom (42%) was substantially higher than that for 2‐hour pain freedom (14%) in this trial,5 as has been observed in other trials,6, 7 which may increase the number of trial participants necessary to show freedom for both endpoints. Further work is required to elucidate if this concordance rate is maintained across trials.…”
Section: Discussionsupporting
confidence: 47%
“…Galcanezumab, a humanized monoclonal antibody that binds to calcitonin gene-related peptide, belongs to a novel class of molecules specifically designed for migraine prevention, unlike currently available preventives. 31 In two phase 2 32 , 33 and three phase 3 studies, 34 36 treatment with galcanezumab versus placebo led to significant reductions in the number of migraine headache days (MHDs) per month in people with episodic and chronic migraine. Another measure of successful migraine preventive treatment is the reduction of acute medication use for migraine.…”
Section: Introductionmentioning
confidence: 99%
“…In phase 3 studies in patients with episodic and chronic migraine, treatment with galcanezumab led to significant reductions in number of MHDs with acute medication use per month. 34 36 Study CGAJ was a 12-month, open-label study, part of the phase 3 development program for migraine prevention. People with episodic or chronic migraine were included in the study and were assigned to one of two treatment arms, galcanezumab 120 mg (with a loading dose of 240 mg) or 240 mg. 37 Study CGAJ was designed to have fewer clinical research site visits, and patients were allowed to self-administer galcanezumab monthly while collecting outcome measures such as the Patient Satisfaction with Medication Questionnaire–Modified (PSMQ-M) questionnaire, HCRU, and acute medication use for migraine or headache.…”
Section: Introductionmentioning
confidence: 99%